A identidade dos catadores de materiais recicláveis e sua relação na sociedade midiatizada na etapa do pós consumo - Ferraz, Susana Cominato (2019)
This study aimed to investigate the processes of constitution of the social identity of the recycled waste pickers working in cooperatives and / or associations in the mediatized society. From the theoretical pillars of Cultural Studies, from a Latin American perspective, we seek to establish reflections and discussions appropriate to these times of globalized neoliberal capitalism, where thousands of individuals are excluded by society, mainly through unemployment. In this situation of social invisibility, many of these individuals choose to work picking the recyclable waste, categorized in this work as a stage in the post-consumer process. Through this activity, they find a way of living, a way to relate and communicate with the same society that excluded them, thus constituting the identity of picker. United in cooperatives and/or associations, these individuals play a role that is related to the cleanliness of cities and the preservation of the environment, which sometimes results in their valorization by society, through public policies and private actions. In the study, we investigated eleven pickers during the work in cooperatives and/or associations, located in different regions of the city of São Paulo, through a qualitative methodological approach, to be able to understand the social and cultural relations of the subjects in their daily life. The interviews, semi-structured and individual, involved questions about the life and work of picking recyclables. With this methodology, we were able to evidence several socio-communicative interactions of the respondents, including their modes of material, symbolic and media consumption. In our conclusions, we observed possible attributes of constitution of the identity of the picker, among them: professional valorization and collective integration through sociocommunicative actions. We emphasize that this study took place under the prism of communication and consumption, understanding that communication plays a fundamental role in contemporary society, structuring the daily life of the subjects, such as the pickers, and even influencing the constitution of their identity. As for consumption, its relevance lies at the heart of the object in question, the social identity of the picker. The pickers are those who interact with the remains of the consumption, with the so-called garbage, picking, sorting and making available the recycable waste (packaging and other materials) for the processes of recycling and reuse post consumption, and, therefore, making possible a new consumption.